2008
DOI: 10.1074/jbc.m709938200
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Role of Fetuin-A and Acidic Serum Proteins in the Formation and Stabilization of Calcium Phosphate Particles

Abstract: The serum protein fetuin-A is a potent systemic inhibitor of soft tissue calcification. Fetuin-A is highly effective in the formation and stabilization of protein-mineral colloids, referred to as calciprotein particles (CPPs). These particles ripen in vitro in a two-step process, indicated by a morphological conversion from spheres to larger prolate ellipsoids. Using a combined light scattering and electron microscopic imaging approach we determined that the second-stage particles resulted from a highly anisot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
216
1
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 197 publications
(235 citation statements)
references
References 47 publications
12
216
1
6
Order By: Relevance
“…When trapped in body compartments, primary CPPs can undergo transition to secondary CPPs, which was shown in a case of progressive calcifying peritonitis 7,23 and cases of amputated limbs of diabetic patients. 24 A weakness of our method is that, as a serum test, it does not by nature take into account the established contribution of cells, including vascular smooth muscle cells 25 and calcifying myeloid cells, 26 in promoting vascular calcifications in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When trapped in body compartments, primary CPPs can undergo transition to secondary CPPs, which was shown in a case of progressive calcifying peritonitis 7,23 and cases of amputated limbs of diabetic patients. 24 A weakness of our method is that, as a serum test, it does not by nature take into account the established contribution of cells, including vascular smooth muscle cells 25 and calcifying myeloid cells, 26 in promoting vascular calcifications in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 We and others have identified the serum protein fetuin-A as a major systemic inhibitor of calcification. [6][7][8][9] Together with additional blood components, fetuin-A prevents the supersaturated calcium and phosphate from precipitating by forming soluble colloidal protein-mineral nanoparticles. Calcification takes place when this humoral line of defense, inherent in small molecules (particularly pyrophosphate and magnesium) and proteins (particularly fetuin-A and albumin), is overwhelmed.…”
mentioning
confidence: 99%
“…More recent studies have shown that a fetuin-mineral complex is formed in the course of the fetuin-mediated inhibition of apatite growth and precipitation in serum containing increased calcium and phosphate (24,25). Purified fetuin also potently inhibits the growth of apatite crystals from supersaturated solutions of calcium phosphate (12,24).…”
mentioning
confidence: 99%
“…Es miembro de la superfamilia de inhibidores de la cistein proteasa. Es un transportador de factores de crecimiento, que se une al factor de crecimiento transformante-(TGF-b) y a la proteína morfogenética (44,45) . Disminuye la activación de macrófagos y la liberación de citokinas proinflamatorias.…”
Section: Ercunclassified
“…No afecta la mineralización ósea normal. Adicionalmente, inhibe la apoptosis de las células musculares lisas de los vasos sanguíneos (45) . En modelos animales de ERC los ratones CKD-2 mostraron incremento en la producción de inhibidores de Wnt (wingless/integration) como Dickkopf-1 (Dkk1) y esclerostina y disminución de Klotho soluble (46) .…”
Section: Ercunclassified